Internet Marketing as a Factor in Business Development - Musayeva Shoira Azimovna; Usmonova Dilfuza Ilkhomovna; Usmanov Farzod Shokhrukhovich (International Journal on Integrated Education, 2021)
In this article, this feature of doing business on the Internet has been successfully used to track the activities of competitors. A minimal competitive advantage can lead to a significant increase in a firm's market share. The firm can anticipate competitors' actions by exploiting their weaknesses and overcoming their advantages.